2015
DOI: 10.1194/jlr.m055962
|View full text |Cite
|
Sign up to set email alerts
|

Liver-specific loss of lipin-1-mediated phosphatidic acid phosphatase activity does not mitigate intrahepatic TG accumulation in mice

Abstract: This article is available online at http://www.jlr.org states and may be linked to other abnormalities in liver metabolism and function. Indeed, in a subset of individuals, hepatic steatosis can progress to liver injury, dysfunction, and failure. Intrahepatic lipid accumulation is also usually highly correlated with systemic insulin resistance, hyperglycemia, dyslipidemias, and risk of cardiovascular disease. Hepatic steatosis is extremely prevalent in obese individuals, and with the epidemic of obesity, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 54 publications
(65 reference statements)
3
23
0
Order By: Relevance
“…The total levels of PA, DAG, TAG, and major phospholipids, such as PC, PE, PS, and PI, remained largely unchanged, similar to a previous report that liver-specific LPIN1 knockout did not alter the global levels of PA, DAG, and phospholipids (35). The levels of PA and DAG in both HCC1806 cells expressing shLuc and shLPIN1 were very low compared with other cell types (26,35,36), implying that they are actively converted to other lipids in these cells (31,32). In contrast to unchanged total lipid levels, significant changes were observed in the compositions of most lipid classes in LPIN1knockdown cells (Fig.…”
Section: Lipin-1 Is Necessary For Membrane Lipid Remodeling But Not Fsupporting
confidence: 89%
See 1 more Smart Citation
“…The total levels of PA, DAG, TAG, and major phospholipids, such as PC, PE, PS, and PI, remained largely unchanged, similar to a previous report that liver-specific LPIN1 knockout did not alter the global levels of PA, DAG, and phospholipids (35). The levels of PA and DAG in both HCC1806 cells expressing shLuc and shLPIN1 were very low compared with other cell types (26,35,36), implying that they are actively converted to other lipids in these cells (31,32). In contrast to unchanged total lipid levels, significant changes were observed in the compositions of most lipid classes in LPIN1knockdown cells (Fig.…”
Section: Lipin-1 Is Necessary For Membrane Lipid Remodeling But Not Fsupporting
confidence: 89%
“…4). One explanation is that these 2 lipids are actively metabolized in HCC1806 cells, which can be partially supported by our finding that both PA and DAG are in very low abundance in HCC1806 cells, as compared to those in other cells (26, 35, 36). In addition to its function as a PAP on the ER that regulates phospholipid synthesis, lipin‐1 can function as a transcriptional coactivator to regulate the expression of genes for fatty acid oxidation (20, 28).…”
Section: Discussionsupporting
confidence: 65%
“…1B). That protein lacks 115 aa of the N terminus of lipin 1, and the resulting protein is deficient in PAP activity but retains transcriptional regulatory function (19,25). Accordingly, compared with WT littermate controls, PAP activity in the tissues of MCK-Lpin1 D115 mice was greatly diminished in skeletal muscle and heart (Fig.…”
Section: Characterization Of Lipin 1 Protein In Mouse Modelsmentioning
confidence: 97%
“…Hepatocyte-specific lipin 1 deletion causes increased susceptibility to alcohol-induced hepatic steatosis, potentially through reduced activation of PGC-1α and fatty acid oxidation [111]. It was also shown that loss of lipin 1 PAP activity does not prevent TAG accumulation in liver in response to dietary lipid overload, possibly related to compensation by the other lipin family members expressed in liver [112]. In contrast to the results with manipulation of lipin 1 in hepatocytes, deletion of lipin 1 in myeloid cells reduces inflammation associated with alcohol-induced steatosis [113].…”
Section: Mouse Models To Study the Physiology Of Glycerolipid Metabmentioning
confidence: 99%